A particle of dread a play - Shepard, Sam 1943-2017 (Vintage Books, 2017)
"In A Particle of Dread, Sam Shepard takes one of the most famous plays in history...Oedipus Rex...and transforms it into a modern American classic. In this telling, Oedipus, King of Thebes, prophesized to kill his father and marry his mother, alternates between his classical identity and that of contemporary "Otto." His wife (and true mother), Jocasta, is also called Jocelyn, and his antagonist (and true father) is split into three characters, Laius, Larry, and Langos. Two present-day policemen from the Southwest stand in for the Greek chorus as they investigate the murder case. Dazzlingly inventive, ringing with the timelessness of myth, A Particle of Dread is an unforgettable work that grapples with questions of storytelling and destiny...the narratives that we pass down, and how they shape our lives. It is a play that lingers in the mind long after we finish the last scene"...